2009
DOI: 10.1139/h09-060
|View full text |Cite
|
Sign up to set email alerts
|

Are Canadians meeting the guidelines for moderate and vigorous leisure-time physical activity?

Abstract: The purpose of this study was to determine the proportion of Canadian adults (aged 18-55 years) who met the guidelines for moderate and vigorous physical activity set out in Canada's Physical Activity Guide to Healthy Active Living. Leisure-time physical activity energy expenditure from moderate- and vigorous-intensity activities was calculated using data from the National Population Health Surveys (1994-1998) and the Canadian Community Health Surveys (2001-2007). The prevalence was estimated for no leisure-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 11 publications
(6 reference statements)
3
18
0
Order By: Relevance
“…The concentrated efforts aimed at reaching high risk ethnicities supports the notion that the PRE-PAID questionnaire provides a unique and appropriate tool for use in public health screening initiatives that target these populations. Another limitation of this investigation is the fact that all responses to the risk questionnaire were self-reported and several studies have shown that individuals tend to under-report their weight and waist circumference [21, 22] while over-reporting their physical activity habits [23, 24]. Although this may be a limitation, it is important to realize that during many public health initiatives, questionnaires are distributed in a similar manner and self-reported data is easier and less expensive to obtain when compared to actual measurement of the various risk factors assessed on the PRE-PAID questionnaire which may require equipment and trained personnel.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrated efforts aimed at reaching high risk ethnicities supports the notion that the PRE-PAID questionnaire provides a unique and appropriate tool for use in public health screening initiatives that target these populations. Another limitation of this investigation is the fact that all responses to the risk questionnaire were self-reported and several studies have shown that individuals tend to under-report their weight and waist circumference [21, 22] while over-reporting their physical activity habits [23, 24]. Although this may be a limitation, it is important to realize that during many public health initiatives, questionnaires are distributed in a similar manner and self-reported data is easier and less expensive to obtain when compared to actual measurement of the various risk factors assessed on the PRE-PAID questionnaire which may require equipment and trained personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that compliance rates were lower for vigorous physical activity as compared to moderate physical activity [14,18,23]. However, these studies used self-reports of physical activity and primarily focused on leisure time.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies have relied on self-reports and often focused on leisure time physical activity (LTPA) [14,20,23,24]. However, these measures ignore everyday activities performed for the purpose of work, transport or household chores.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas objectively measured physical activity showed significant associations with cardiovascular disease risk factors [16], the time-by-intensity based calculations did not [24]. The Canadian Health Measures Survey reported that only 15% of Canadian adults (17% of men, 14% of women) engaged in 150 minutes or more per week of at least moderately vigorous physical activity in bouts of 10 minutes or longer when objectively measured [8], which is considerably less than the estimated 65% of Canadian adults who met the guidelines for physical activity in 2007 from self-reported time and intensity [5]. Doubly labeled water, among the best objective measured of physical activity, is reported have a correlation of r=0.2 with time-by-intensity physical activity estimates from questionnaires [18], which is substantially less than its correlations of r=0.5 and r=0.6 with energy expenditure from activity monitors [3,22].…”
Section: Discussionmentioning
confidence: 99%